Cervical muscle strength and motor control assessment using dynamometry and surface electromyography in women with migraine and chronic migraine: a controlled study - Florencio, Lidiane Lima (2017)
Objectives: to verify if women with migraine present altered neck muscles function and altered muscle activity in comparison to non-headache subjects. Moreover, we aimed to identify if there is any relationship between neck muscles dysfunction and the chronicity of migraine attacks. Methods: women with migraine, stratified by episodic and chronic, and age-matched non headache women were the subject of the current thesis. Neck pain relateddisability was assessed by the Neck Disability Index. Neck muscles strength was assessed by a customized hand-held dynamometer. Myoelectrical signals of the sternocleidomastoid, anterior scalene, splenius capitis and upper trapezius were assessed using surface electromyography. Experimental conditions involved maximal isometric voluntary contractions in flexion, extension and lateral bending directions and; craniocervical flexion test, a low load test applied to verify deep cervical flexors ability to supply adequate cervical spine stability. Finally, identification of myofascial trigger points and head and cervical posture photogrammetric evaluation were made in order to be correlated to the muscles electrical activity in the craniocervical flexion test. Results: Although both groups presents high prevalence of neck related disability, subjects with chronic migraine are more likely to report neck related disability, especially the most disabling forms, than episodic migraine. Episodic migraine demonstrated to different neck muscle control only under maximal voluntary tasks. Chronic migraine presented alterations in comparison with controls at maximal conditions, i.e., lower extension force; more time to produce maximal force; greater antagonist coactivation and greater fatigability. During craniocervical flexion test, chronic migraine also differs from control group presenting greater activity of neck extensors. Presence of active trigger points in neck muscles and extended head posture can influence the neck muscles activity during the craniocervical flexion test. Conclusions: migraine is associated to a deterioration of neck muscles functions and to an altered motor control. We can assume an interaction between chronicity of migraine frequency and cervical dysfunction, specially related to neck extensors. More severe disabilities and the majority of the altered function or motor control could only be evidenced in the chronic form